The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1305049110
|View full text |Cite
|
Sign up to set email alerts
|

Random network peristalsis in Physarum polycephalum organizes fluid flows across an individual

Abstract: Individuals can function as integrated organisms only when information and resources are shared across a body. Signals and substrates are commonly moved using fluids, often channeled through a network of tubes. Peristalsis is one mechanism for fluid transport and is caused by a wave of cross-sectional contractions along a tube. We extend the concept of peristalsis from the canonical case of one tube to a random network. Transport is maximized within the network when the wavelength of the peristaltic wave is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
168
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 36 publications
7
168
0
6
Order By: Relevance
“…Although the chemical nature of the signaling molecule so far remains unidentified the discovery of the mechanism of signal propagation itself allows us to understand P. polycephalum's complex dynamics. The mechanism implies that the peristaltic wave matches organism size, explaining our previous observation (12). Moreover the mechanism, working in tandem with tube radius adaptation in response to the increased flow, seems sufficient to explain how P. polycephalum is able to solve a maze and build efficient transport networks.…”
Section: Significancesupporting
confidence: 57%
See 2 more Smart Citations
“…Although the chemical nature of the signaling molecule so far remains unidentified the discovery of the mechanism of signal propagation itself allows us to understand P. polycephalum's complex dynamics. The mechanism implies that the peristaltic wave matches organism size, explaining our previous observation (12). Moreover the mechanism, working in tandem with tube radius adaptation in response to the increased flow, seems sufficient to explain how P. polycephalum is able to solve a maze and build efficient transport networks.…”
Section: Significancesupporting
confidence: 57%
“…Building on our previous observations (12,18), we now report and characterize the mechanism of communication in P. polycephalum and demonstrate that a simple feedback between a signaling molecule and a propagating contraction front is sufficient to explain P. polycephalum's sophisticated behaviors. The key experiment demonstrates that a localized nutrient stimulus…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…10 Research frontiers are also oriented towards hybrid systems, where biological systems are key components of electronic devices. [11][12][13] For example, the adaptive 'learning' behavior of slime mould Physarum polycephalum (PPM) was described in terms of memristor model; 14,15 the mould also resulted to be able to perform complex tasks of the information processing. [16][17][18] Gale et al 19 observed occasionally that PPM protoplasmic tubes showed hysteretic current-voltage characteristics, consistent with those of the memristive systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this mode of growth, P. polycephalum is actively motile (has been observed moving up to 10 mm per hour) and will search for food sources. In addition, it will also lay down protoplasmic tubes to connect any food sources and re-direct nutrients though the protoplasmic tubes by peristalsis (Alim et al, 2013) to the most active regions of the organism. P. polycephalum has been shown to be sensitive to bright light (Ueda et al, 1988) and specific chemical cues (Costello and Adamatzky, 2013), which have been used to control the direction of plasmodium locomotion.…”
Section: Introductionmentioning
confidence: 99%